2013
DOI: 10.1021/am4030406
|View full text |Cite
|
Sign up to set email alerts
|

Copper Shell Networks in Polymer Composites for Efficient Thermal Conduction

Abstract: Thermal management of polymeric composites is a crucial issue to determine the performance and reliability of the devices. Here, we report a straightforward route to prepare polymeric composites with Cu thin film networks. Taking advantage of the fluidity of polymer melt and the ductile properties of Cu films, the polymeric composites were created by the Cu metallization of PS bead and the hot press molding of Cu-plated PS beads. The unique three-dimensional Cu shell-networks in the PS matrix demonstrated isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 32 publications
0
47
0
3
Order By: Relevance
“…The colorlessness of these matrices gives quasi-metallic colored silver-dispersed composite films. First, in case of a high content of conductive fillers like copper or silver, the electric conductivity could become a dominant factor for enhanced λ  of composites [12]. However, experimental volume resistivity of the SD/Ag film with =46 vol% was measured as 6.19×10 -5 Ω·cm.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colorlessness of these matrices gives quasi-metallic colored silver-dispersed composite films. First, in case of a high content of conductive fillers like copper or silver, the electric conductivity could become a dominant factor for enhanced λ  of composites [12]. However, experimental volume resistivity of the SD/Ag film with =46 vol% was measured as 6.19×10 -5 Ω·cm.…”
Section: Measurementsmentioning
confidence: 99%
“…In contrast, the Ag-MPs dispersed in SD/Ag are obviously agglomerated compared with SIM/Ag, and high contrast densities can be observed in the cross-sectional SEM images. Yu et al [12] recently reported that polymer composites with three-dimensional Cu thin film networks have isotropic and enhanced conductivity at low Cu contents. Since the λ  of metallic silver is much higher than those of PIs, these results indicate that the abrupt increase in λ  observed for SD/Ag and b-SF/Ag above  =30 vol% was induced by spontaneous formation of thermal conductive paths of Ag-MPs in the film.…”
Section: Measurementsmentioning
confidence: 99%
“…Fig. 20 The fabrication process of Cu-p-PS composites [139] obtained λ value of the Al 2 O 3 /PMMA hybrid materials was in the range of 0.5-2.5 W/mK and the λ value along the layers than that of across the layers.…”
Section: Thermally Conductive/insulating Fillersmentioning
confidence: 99%
“…Huang et al [138] prepared a series of thermally conductive Ag/PVDF nanocomposites, and the obtained λ value of the Ag/PVDF nanocomposite with 20 vol% Ag was significantly improved to 6.5 W/mK. Yu et al [139] reported a novel method to fabricate Cu-plated polystyrene (Cu-p-PS) composites with Cu thin film networks, created by the Cu metallization of PS bead and the hot press molding of Cu-plated PS beads (Fig. 20).…”
Section: Metal Fillersmentioning
confidence: 99%
“…In order to overcome this problem, a variety of methods have been developed to improve the thermal conductivity. A traditional method is to introduce high contents of thermally conductive fillers, such as metals 611 , ceramic particles 1215 , carbon nanotubes 1620 , or graphene nanoplateles 2125 . In particular, the silicon carbides are provided with excellent properties such as high thermal conductivity, high thermal stability, high breakdown field, excellent mechanical properties and chemical inertness 2632 .…”
Section: Introductionmentioning
confidence: 99%